Hubungan Penerimaan Seksual terhadap Kepuasan Penggunaan Kontrasepsi di wilayah Kabupaten Paser Provinsi Kalimantan Timur - Muhammad Dwi Kurniawan; Devuna Puspa Wulandari; Alifa Dinda Nurrina; Laksmita Dewi Adzillina; Ema Suliyusti (Lembaga Pengembangan Kinerja Dosen, 2026)
Sexual aspects play a crucial role in the long-term success of family planning programs, necessitating their inclusion in all related interventions and policies. Health service providers must be equipped with sufficient knowledge and skills to openly and sensitively discuss the sexual effects of various contraceptive methods. Furthermore, gender biases that hinder communication regarding women’s sexual rights should be addressed to ensure family planning programs provide more optimal and inclusive benefits. This study aims to examine the correlation between contraceptive use among mothers and the intensity of sexual relations among couples in the working area of Community Health Centers across Paser Regency. The study employed an observational design with a survey technique conducted among 320 family planning acceptor couples. Data were collected through questionnaires and observation, and analyzed using Chi-square tests. The findings reveal a fairly even distribution of sexual intensity across age groups, with no significant negative correlation between the use of oral contraceptive pills and sexual activity intensity (p=0.18). The study concludes that the use of contraceptive pills does not significantly affect the decrease in sexual frequency or intensity, suggesting that other factors such as individual characteristics and social context should be considered in evaluating sexual satisfaction among family planning acceptors.